The Use of 3D Pageflip Professional Electronic Student Worksheets on the Protist Concept on the Learning Outcomes of Grade X Senior High School Students - Isra Melliyanti Putri; Aminuddin Prahatama Putra; Muhammad Zaini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Currently, the success rate of students in schools is still lacking in learning the subject matter. Therefore, the authors conducted research on the use of 3D Pageflip Professional electronic student worksheets on the concept of protists on the learning outcomes of students in grade X high school. The purpose of this study is to describe the effect of using the 3D Pageflip Professional electronic student worksheet on the Protists concept on (1) product cognitive learning outcomes (2) cognitive learning outcomes of students in grade X high school. The design of this research is quasi-experimental and the design is The Nonequivalent control group design. The research sample is grade X-PMIA 1 and X-PMIA 2 as the experimental group, grade X-PMIA 3 as the control group. The research instrument uses multiple choice tests to measure product cognitive learning outcomes and process cognitive. The hypothesis data analysis technique is the Independent Samples Test from the pre-posttest. From the research, the results showed that there was an effect on the use of 3D Pageflip Professional electronic student worksheets on (1) cognitive learning outcomes of students' products with sig. (2-tailed) 0.017 (2) cognitive learning outcomes of students with sig. (2-tailed) 0.041. From the results of the study, it is suggested that the evaluation tool needs to be improved to make it look more effective in improving product cognitive and student learning outcomes.AbstrakSekarang ini tingkat keberhasilan dari peserta didik di sekolah masih dinyatakan kurang dalam mempelajari materi pelajaran. Maka dari itu penulis melakukan penelitian penggunaan e-LKPD 3D Pageflip Professional pada konsep protista terhadap hasil belajar peserta didik kelas X SMA. Tujuan dari penelitian ini yaitu untuk mendeskripsikan pengaruh penggunaan e-LKPD 3D Pageflip Professional pada konsep Protista terhadap (1) hasil belajar kognitif produk (2) hasil belajar kognitif proses peserta didik kelas X SMA. Rancangan penelitian ini yaitu quasi experiment dan desainnya yaitu The Nonequivalent control group design. Sampel penelitian yaitu kelas X PMIA 1 dan X PMIA 2 sebagai kelompok eksperimen, kelas X PMIA 3 sebagai kelompok kontrol. Instrumen penelitiannya menggunakan tes pilihan ganda untuk mengukur hasil belajar kognitif produk dan kognitif proses. Teknik analisis data hipotesisnya dengan uji Independent Samples Test dari pre-posttest. Dari penelitian didapatkan hasil yaitu terdapat pengaruh penggunaan e-LKPD 3D Pageflip Professional terhadap (1) hasil belajar kognitif produk peserta didik dengan sig. (2-tailed) 0.017 (2) hasil belajar kognitif proses peserta didik dengan sig. (2-tailed) 0.041. Dari hasil penelitian, disarankan perlu penyempurnaan terhadap alat evaluasi agar terlihat lebih efektif pengaruhnya dalam meningkatkan kognitif produk dan kognitif produk hasil belajar peserta didik.